THE SYNDROME OF LEFT VENTRICLE HYPERTROPHY - S. L. Dzemeshkevitch; E. V. Zaklyasminskaya; Yu. V. Frolova (Российский кардиологический журнал, 2014)
Authors, based on their own experience of the left ventricle hypertrophy treatment, I and by modern literature exploration di analyze three leading diseases, in phenotype of those the left ventricle hypertrophy and its typical central hemodynamic disorders I play crucial role. Arterial hypertension, involutionary calcified aortic stenoses, 1 bicuspid aorto-valvulopathy, hypertrophic cardiomyopathy totally hold leading position in the structure of cardiovascular modbidity. Having the same phenotypical I marks, these diseases absolutely different by their genetic disorders and, I respectively, require completely different treatment strategies. Taking into account the social influence of the left ventricle hypertrophy syndrome due to its prevalence, a serious epidemiological studies on the national level are required.